Integration of Business Intelligence Dashboard for Enhanced Data Analytics Capabilities - Ghaffar, Anza (My University, 2020)
Digitilization has taken the world by storm which has lead to the development of automation and smart technologies which are driven by data and in return are generating even more data. With the volume of data being created it has become essential to store and analyze the data through which better decisions can be taken. It is not just essential to store this data the real benefit lies if we can convert this data into information through which knowledge can be gained for actionable insights. This the where the Business Intelligence and Data Analytics ecosystem has a very crucial part to play. In this research first we do a pre-study of the process involved in building BI ecosystem and the features that are offered by the BI tools SaaS and if there are options other than BI SaaS which could help in delivering the same value. This research also includes how BI and DA are related to each other and which one is important in what scenario. Lastly we study the criteria which should be taken into account while choosing and BI tool and a comparison of how the best available BI SaaS tools compete with each other along with their strengths and weaknesses. The BI SaaS tools compared in the pre-study are then used to develop Interactive Dashboards to get a more of a hands on experience with the BI tools and also match the requirements of the case organization for delivering the BI dashboard. Apart from only relying on the BI tool providers we have also developed Interactive Dashboards using open source frameworks to have an in house solution which delivers the same value for the case organization as the other BI tools available in the market. According to this study, BI is a very valuable tool for the organizations for analyzing their data but the decision to choose or develop a BI tool totally depends on the organizations requirements of what do they want to achieve with these tools.
Keywords: visualisation; business intelligence; data mining; information (data); innovations; query languages; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; Master’s Programme in Communication and Systems Engineering